Productivity and efficiency analysis - Greene, William H. 1951-; Khalaf, Lynda; Sickles, Robin; Veall, Michael; Voia, Marcel-Cristian (Cham Springer International Publishing, 2016)
This proceedings volume examines state-of-the art of productivity and efficiency analysis and adds to the existing research by bringing together a selection of the best papers from the 8th North American Productivity Workshop (NAPW). It also aims to analyze world-wide perspectives on challenges that local economies and institutions may face when changes in productivity are observed. The volume comprises seventeen papers that deal with productivity measurement, productivity growth, dynamics of productivity change, measures of labor productivity, measures of technical efficiency in different sectors, frontier analysis, measures of performance, industry instability and spillover effects. These papers are relevant to academia, but also to public and private sectors in terms of the challenges firms, financial institutions, governments and individuals may face when dealing with economic and education related activities that lead to increases or decreases of productivity. The North American Productivity Workshop brings together academic scholars and practitioners in the field of productivity and efficiency analysis from all over the world. It is a four day conference exploring topics related to productivity, production theory and efficiency measurement in economics, management science, operations research, public administration, and related fields. The papers in this volume also address general topics as health, energy, finance, agriculture, utilities, and economic development, among others. The editors are comprised of the 2014 local organizers, program committee members, and celebrated guest conference speakers.
Decompositions of Productivity Growth into Sectoral Effects: Some Puzzles Explained.-The Dynamics of Productivity Change: A Review of the Bottom-Up Approach. A General Error Revenue Function Model with Technical Inefficiency: An Application to Norwegian Fishing Trawler.-Production Response in the Interior of the Production Set.-Spillover Effects of Public Capital Stock using Spatial Frontier Analyses: A First Look at the Data -- Dynamic Technical Efficiency.-Analysing Labour Productivity in Ecuador -- Hierarchical performance and unobservable heterogeneity in health: A dual-level efficiency approach applied to NHS pathology in England.-Is there Evidence of ICT Skill Shortages in Canadian Taxfiler Data?.-Worker Separations and Industry Instability.-Inputs, Productivity and Agricultural Growth in Sub-Saharan Africa.-University Knowledge Spillovers and Innovative Startup Firms.-Accounting for Natural Capital in Productivity of the Mining and Oil and Gas Sector.-Balancing Incentives {8211} The Development and Application of a Regulatory Benchmarking Model.-Limitations of the Approximation Capabilities of the Translog Model: Implications for Energy demand and Technical Change Analysis.-Bosman Ruling Implications on Player Productivity in the English Premier League.-Productivity Measurement, Model Averaging, and World Trends in Growth and Inequality.
Includes bibliographical references at the end of each chapters and index.
Keywords: Industrial productivity -- Congresses; Production management -- Congresses; Econometrics -- Congresses; Public administration -- Congresses; Electronic books